Stress intensity factors analyses for external semi-elliptical crack for repaired gas-pipeline by composite overwrap under pressure (Fracture and Structural Integrity, 2019)
The purpose of this article is to present the stress intensity factors (SIF) solutions for semi-elliptic crack in pipelines under internal pressures, the stress intensity factors are calculated by the three-dimensional finite element method (FEM) for cracked pipelines and repaired pipe by composite patch. The distribution of normalized stress intensity factors (KI, KII and KIII) along the crack front for different crack lengths, crack depth, crack geometry, lap length and composite thickness was obtained by nodal calculations. Our FE results show that the crack frond is non-regular with respect to the rupture mode and presents three zones where the mixed mode (KII) is dominant from the deepest point to the point close to the surface of the pipe not the mode I cited in several studies. When the edge of the crack is close to the outer diameter, the mode III (KIII ) is dominant and this regardless of the state of the pipelines. it can also be noted that the composite repair reduces the SIF KI by 46% and the KII by 55% and the KIII by 72% near the outside diameter of the pipe in each zone of domination. However composite repair is very effective for a rectangular crack as for the semi-elliptical crack. this confirms that the elliptic crack is dominated by the mixed mode II not by mode I.
Keywords: Stress intensity factor; Crack; Composite; Adhesive; Pipeline; API 5L X65